Altered dopamine transmission as a familial risk trait for addictions. (February 2017) - Leyton, Marco
Highlights: Altered dopamine transmission has long been proposed as a risk factor for addictions. Recent studies identify dopamine disturbances in people at risk for addictions. The effects seen in the neuroimaging studies vary considerably. The present review evaluates the strength of the evidence and possible meanings. Abstract : Is altered dopamine transmission a pre-existing vulnerability trait for addiction? Preliminary support for this hypothesis has been provided by recent neuroimaging studies. While most effects remain to be replicated, there is now evidence that, compared to healthy controls, people at familial risk for substance use disorders exhibit both increases and decreases in striatal dopamine function. The following review assesses the strength of this evidence, considers explanations for discrepant results, and discusses potential implications for understanding pathways to addiction.